Powder for additive manufacturing, method for manufacturing powder for additive manufacturing, additive manufacturing body, and metal sintered body
By coating the coupling agent with specific functional groups on the surface of the metal powder to form a thin film, the problem of poor fluidity and adhesion in high temperature and high humidity environments is solved, and the high accuracy and reusability of the 3D printing model are achieved.
Patent Information
- Application Number
- JP2021019770
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-10
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2041-02-10
AI Technical Summary
In the prior art, the fluidity of metal powder surface treatment agents decreases in high temperature or high humidity environments, resulting in poor dimensional accuracy and reusability of 3D printing models.
The metal powder containing FE, NI or CO system alloy is used to coat the film formed by a coupling agent containing specific functional groups to ensure that the powder maintains fluidity and adhesion in a high temperature and high humidity environment, and forms a stable chemical bond through the reaction of the coupling agent with the hydroxyl group on the surface of the metal powder.
It improves the flowability and adhesion of metal powder in high temperature and high humidity environments, ensures the high accuracy and reusability of the 3D printing model, and reduces the density changes of the model during the heat treatment process.
Smart Images

Figure 0007622459000016 
Figure 0007622459000017 
Figure 0007622459000018
Abstract
Description
[Technical field]
[0001] The present invention relates to a powder for additive manufacturing, a method for producing the powder for additive manufacturing, an additive manufactured body, and a metal sintered body. [Background technology]
[0002] In recent years, additive manufacturing using metal powder has become popular as a technique for forming three-dimensional objects. This technique involves the steps of calculating the cross-sectional shape of the three-dimensional object when it is thinly sliced along a plane perpendicular to the lamination direction, forming a powder layer by smoothing the metal powder into layers, and solidifying a part of the powder layer based on the shape calculated. The three-dimensional object is formed by repeating the steps of forming the powder layer and solidifying the part.
[0003] Known methods for forming three-dimensional objects include fused deposition molding (FDM), selective laser sintering (SLS), binder jetting, and the like, depending on the solidification principle.
[0004] Patent Document 1 discloses a method for manufacturing an EB sintered 3D printer molded product using an electron beam (EB) instead of a laser as a modified example of the powder sintering layered molding method. This method is a method for manufacturing a metal molded product by layering surface-treated metal powder for EB sintered 3D printers, optionally preheating, and then sintering by EB irradiation. The surface-treated metal powder for EB sintered 3D printers is a powder in which the surface of a metal powder manufactured by a known method is surface-treated with a coupling agent. By using such surface-treated metal powder, the conductivity during layering is improved. Therefore, sintering can be performed favorably by EB. In addition, partial sintering can be suppressed by preheating. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2017-25392 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, the surface-treated metal powder described in Patent Document 1 has a problem in that its fluidity decreases at high temperatures or when it absorbs moisture. If the fluidity decreases at high temperatures, for example, when the surface-treated metal powder is heated during additive manufacturing using a 3D printer, it becomes difficult to reuse it. Even if it is used, it will result in a decrease in the dimensional accuracy of the molded object. [Means for solving the problem]
[0007] The powder for additive manufacturing according to the application example of the present invention is A powder for additive manufacturing used to form a powder layer for additive manufacturing, A metal powder composed of an Fe-based alloy, a Ni-based alloy, or a Co-based alloy; A functional group is provided on the surface of the metal powder particles. and hydrolyzable groups Coupling agent having reacts with the particle surface A coating including a compound; Equipped with The average particle size is 3.0 μm or more and 30.0 μm or less, The functional group contains a cyclic structure-containing group, a fluoroalkyl group, or a fluoroaryl group, the compound contains a covalent bond formed by a dehydration condensation reaction between a hydrolyzate of the hydrolyzable group and a hydroxyl group formed on the particle surface, When the sample is spread over a double-sided tape to prepare a test specimen, the test specimen has a contact angle with water of 95° or more.
[0008] A method for producing a powder for additive manufacturing according to an application example of the present invention includes: 1. A method for producing an additive manufacturing powder used to form a powder layer for additive manufacturing, comprising the steps of: Consists of Fe-based alloy, Ni-based alloy or Co-based alloy Providing a metal powder; reacting a coupling agent having a functional group with the metal powder to adhere the coupling agent to the surfaces of the particles of the metal powder; The metal powder to which the coupling agent is attached is heated to form a coating on the surface of the particles; The above Obtaining a powder for additive manufacturing; having The average particle size of the powder for additive manufacturing is 3.0 μm or more and 30.0 μm or less, The functional group contains a ring structure-containing group, a fluoroalkyl group, or a fluoroaryl group. death, When the powder for additive manufacturing is spread on a double-sided tape to form a test specimen, the test specimen has a water contact angle of 95° or more. .
[0009] The layered object according to the application example of the present invention is Powder for additive manufacturing according to an application example of the present invention; A binder that binds particles of the powder for additive manufacturing together; The present invention is characterized by having the following.
[0010] The metal sintered body according to the application example of the present invention is The present invention is characterized in that it is a sintered body of the layered manufacturing body according to an application example of the present invention. [Brief description of the drawings]
[0011] [Figure 1] 1 is a flowchart for explaining a method for manufacturing a layered object. [Diagram 2] 1A to 1C are diagrams for explaining a method for manufacturing a layered object according to an embodiment. [Diagram 3] 1A to 1C are diagrams for explaining a method for manufacturing a layered object according to an embodiment. [Figure 4] 1A to 1C are diagrams for explaining a method for manufacturing a layered object according to an embodiment. [Diagram 5] 1A to 1C are diagrams for explaining a method for manufacturing a layered object according to an embodiment. [Figure 6] 1A to 1C are diagrams for explaining a method for manufacturing a layered object according to an embodiment. [Figure 7] 1A to 1C are diagrams for explaining a method for manufacturing a layered object according to an embodiment. [Figure 8] 1A to 1C are diagrams for explaining a method for manufacturing a layered object according to an embodiment. [Figure 9] 1A to 1C are diagrams for explaining a method for manufacturing a layered object according to an embodiment. [Figure 10] 1A to 1C are diagrams for explaining a method for manufacturing a layered object according to an embodiment. [Figure 11] FIG. 1 is a cross-sectional view illustrating a powder for additive manufacturing according to an embodiment. [Figure 12] 1 is a flowchart for explaining a method for producing a powder for layered manufacturing according to an embodiment. [Figure 13] FIG. 1 is a table showing a schematic diagram of the state of a coupling agent containing a trialkoxy group after hydrolysis and before reaction with hydroxyl groups generated on the surface of metal particles, the state immediately after the formation of a coating, and the state after the functional groups contained in the coating are thermally decomposed. [Figure 14] 1 is a graph comparing the bulk density of the powder of Comparative Example 1, the powder of the Reference Example, and the powder of Example 1. [Figure 15] 1 is a graph showing the relationship between the bulk density of the powder of Example 1 and the powder of Comparative Example 1 and the heating time, with the horizontal axis representing the heat treatment time and the vertical axis representing the bulk density. [Figure 16] 1 is a graph comparing the tap density of the powder of Comparative Example 1, the powder of the Reference Example, and the powder of Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, preferred embodiments of the powder for additive manufacturing, the method for producing the powder for additive manufacturing, the additive manufactured body, and the metal sintered body of the present invention will be described in detail with reference to the accompanying drawings.
[0013] 1. Manufacturing method for additive manufacturing First, a method for producing a layered object will be described. Fig. 1 is a flow chart for explaining the method for producing a layered object, and Figs. 2 to 10 are views for explaining the method for producing a layered object according to the embodiment.
[0014] The method for manufacturing an additive manufacturing object shown in Fig. 1 to Fig. 10 is a method called a binder jetting method, and includes a powder layer forming step S01, a binder solution supplying step S02, and a repeating step S03, as shown in Fig. 1. In the powder layer forming step S01, powder 1 for additive manufacturing is spread to form a powder layer 31. In the binder solution supplying step S02, a binder solution 4 is supplied to a predetermined area of the powder layer 31 to bond the particles in the powder layer 31 together, thereby obtaining a bonded layer 41. In the repeating step S03, the powder layer forming step S01 and the binder solution supplying step S02 are repeated once or twice or more times to obtain an additive manufacturing object 5. Each step will be described in order below.
[0015] 1.1.Additive manufacturing equipment First, prior to describing the powder layer forming step S01, the layered manufacturing apparatus 2 will be described. The additive manufacturing device 2 comprises an apparatus main body 21 having a powder storage section 211 and a modeling section 212, a powder supply elevator 22 provided in the powder storage section 211, a modeling stage 23 provided in the modeling section 212, and a coater 24 and a solution supply section 25 movably arranged on the apparatus main body 21.
[0016] The powder storage section 211 is provided in the device body 21 and is a recess with an open top. The powder 1 for layered manufacturing is stored in the powder storage section 211. An appropriate amount of the powder 1 for layered manufacturing stored in the powder storage section 211 is supplied to the modeling section 212 by the coater 24.
[0017] A powder supply elevator 22 is disposed at the bottom of the powder storage section 211. The powder supply elevator 22 is capable of moving in the vertical direction in Figs. 2 to 9 with the powder 1 for additive manufacturing placed on it. By moving the powder supply elevator 22 upward, the powder 1 for additive manufacturing placed on the powder supply elevator 22 is pushed up and caused to overflow from the powder storage section 211. As a result, the overflowing powder 1 for additive manufacturing can be moved toward the modeling section 212 as described below.
[0018] The modeling section 212 is a recessed section that is provided in the device body 21 and is open at the top. In this modeling section 212, the powder 1 for layered modeling that is supplied from the powder reservoir 211 is spread in the form of a layer.
[0019] In addition, a modeling stage 23 is disposed at the bottom of the modeling section 212. The modeling stage 23 is movable in the up and down directions in Fig. 2 to Fig. 9 with the powder 1 for additive manufacturing spread thereon. By appropriately setting the height of the modeling stage 23, the amount of the powder 1 for additive manufacturing spread on the modeling stage 23 can be adjusted.
[0020] The coater 24 is provided so as to be movable in the left-right direction in FIGS. 2 to 9 from the powder storage section 211 to the modeling section 212 .
[0021] The solution supplying unit 25 is composed of, for example, an inkjet head or a dispenser, and is two-dimensionally movable in the left-right direction and the thickness direction of the paper in Figures 2 to 9 in the modeling unit 212. The solution supplying unit 25 can supply a desired amount of binder solution 4 to a desired position.
[0022] 1.2. Powder layer formation process Next, the powder layer forming step S01 using the above-mentioned additive manufacturing device 2 will be described. In the powder layer forming step S01, the additive manufacturing powder 1 is spread on the modeling stage 23 to form a powder layer 31. Specifically, as shown in FIG. 2 and FIG. 3, the additive manufacturing powder 1 stored in the powder storage section 211 is dragged onto the modeling stage 23 using a coater 24 to be uniform in thickness. This results in the powder layer 31 shown in FIG. 4. At this time, the thickness of the powder layer 31 can be adjusted by setting the upper surface of the modeling stage 23 slightly lower than the upper end of the modeling section 212. Note that the additive manufacturing powder 1 according to this embodiment is a powder with high fluidity, as described later. Therefore, a powder layer 31 with a high filling rate can be obtained.
[0023] 1.3. Binder solution supply process 5, in the binder solution supplying step S02, the binder solution 4 is supplied by the solution supplying unit 25 to a desired region of the powder layer 31. This causes particles in the region of the powder layer 31 to which the binder solution 4 has been supplied to be bonded together to obtain a bonded layer 41. The bonded layer 41 is formed by bonding particles of the powder 1 for additive manufacturing together with the binder, and has a shape retention that is sufficient to prevent the powder from breaking under its own weight or greater.
[0024] The binder layer 41 may be heated simultaneously with or after the supply of the binder solution 4. This promotes the evaporation of the solvent contained in the binder solution 4 and promotes the binding of particles together due to the solidification or hardening of the binder. When the binder contains a photocurable resin or an ultraviolet-curable resin, light irradiation or ultraviolet irradiation may be performed instead of or in addition to heating.
[0025] The heating temperature in the case of heating is not particularly limited, but is preferably from 50° C. to 250° C., and more preferably from 70° C. to 200° C. As a result, when reusing the powder for additive manufacturing 1 that has not been bound by the binder solution 4, it is possible to sufficiently volatilize the solvent and solidify or harden the binder while suppressing denaturation of the powder for additive manufacturing 1 caused by heating.
[0026] The binder solution 4 is not particularly limited as long as it is a liquid having a component with tackiness or adhesiveness capable of binding particles of the powder for additive manufacturing 1 together. As an example, the solvent of the binder solution 4 may be, for example, water, alcohols, ketones, carboxylates, etc., and may be a mixed liquid containing at least one of these. In addition, the solute of the binder solution 4, i.e., the binder, may be, for example, fatty acid, paraffin wax, microwax, polyethylene, polypropylene, polystyrene, acrylic resin, polyamide resin, polyester, stearic acid, polyvinylpyrrolidone (PVP), polyvinyl alcohol (PVA), polyethylene glycol (PEG), etc.
[0027] 1.4.Repetitive process In the repeating step S03, the powder layer forming step S01 and the binder solution supplying step S02 are repeated one or more times. This allows the binder layer 41 to be built up to a required height. Specifically, as shown in Figs. 6 and 7, a new powder layer 32 is formed on the formed binder layer 41. Next, as shown in Fig. 8, the binder solution 4 is supplied to a desired region of the powder layer 32 by the solution supplying unit 25. This causes the particles in the region of the powder layer 32 to which the binder solution 4 is supplied to be bound together, thereby obtaining the binder layer 42. The binder layer 42 is formed by binding the particles of the powder 1 for additive manufacturing together with the binder, and has a shape retention that is not broken by its own weight or more. By repeating the formation of such powder layer 32 and binder layer 42, an additive manufacturing body 5 having a desired shape is obtained, as shown in Fig. 9. The layered object 5 is an assembly of bonding layers including the bonding layer 41 and the bonding layer 42, and the powder for layered object 1 that does not constitute the layered object 5 is collected and reused as necessary.
[0028] 2. Manufacturing method of metal sintered body Next, a method for producing a metal sintered body using the layered shaped body obtained as described above will be described. First, the layered model 5 is removed from the modeling unit 212, and a sintering process is performed on the layered model 5 using a firing furnace or the like. As a result, a metal sintered body 10, which is a sintered body of the layered model 5, is obtained, as shown in FIG.
[0029] When the layered product 5 is sintered, the layered product 5 may be subjected to a degreasing treatment prior to sintering. The degreasing treatment is a treatment in which the layered product 5 is heated to remove at least a part of the binder.
[0030] The sintering process is a process for sintering metal powder particles together by heating the layered product 5 or the degreased layered product 5. An example of the heating conditions is 980°C to 1330°C for 0.2 hours to 7 hours. Examples of the heating atmosphere include air, inert gas, and reduced pressure.
[0031] 3. Powder for additive manufacturing Next, the powder for additive manufacturing according to the embodiment will be described. FIG. 11 is a cross-sectional view that illustrates a powder for additive manufacturing according to an embodiment. The powder for additive manufacturing 1 according to this embodiment is a powder used in various additive manufacturing methods such as the binder jetting method described above.
[0032] The average particle size of the powder 1 for layered manufacturing is 3.0 μm or more and 30.0 μm or less, preferably 4.0 μm or more and 15.0 μm or less, and more preferably 5.0 μm or more and 10.0 μm or less.
[0033] By setting the average particle size of the powder 1 for additive manufacturing within the above range, a metal sintered body 10 with good surface roughness and high dimensional accuracy can be obtained by the additive manufacturing method described above.
[0034] 11, the powder 1 for additive manufacturing has a plurality of surface-coated particles 13 including metal particles 11 constituting the metal powder and a coating 12 covering the surface of the metal particles 11. The powder 1 for additive manufacturing having such surface-coated particles 13 has high fluidity and therefore high filling property when leveled.
[0035] The material constituting the metal particles 11 is not particularly limited and may be any material that has sinterability. Examples include simple substances such as Fe, Ni, Co, and Ti, as well as alloys and intermetallic compounds that contain these as main components.
[0036] Examples of Fe-based alloys include stainless steels such as austenitic stainless steel, martensitic stainless steel, and precipitation hardening stainless steel, low carbon steel, carbon steel, heat resistant steel, die steel, high speed tool steel, Fe-Ni alloys, and Fe-Ni-Co alloys.
[0037] Examples of Ni-based alloys include Ni-Cr-Fe-based alloys, Ni-Cr-Mo-based alloys, and Ni-Fe-based alloys.
[0038] Examples of Co-based alloys include Co-Cr-based alloys, Co-Cr-Mo-based alloys, and Co-Al-W-based alloys.
[0039] Examples of Ti-based alloys include alloys of Ti with metal elements such as Al, V, Nb, Zr, Ta, and Mo, and specific examples include Ti-6Al-4V and Ti-6Al-7Nb.
[0040] The coating 12 is formed by reacting a coupling agent having a functional group with the surface of the metal particle 11. Therefore, the coating 12 contains a compound derived from the coupling agent having a functional group, and exhibits properties derived from the functional group.
[0041] The functional group used may be one containing a cyclic structure, a fluoroalkyl group or a fluoroaryl group.
[0042] The cyclic structure-containing group is a functional group having a cyclic structure. Examples of the cyclic structure-containing group include aryl groups such as a phenyl group, a tolyl group, a xylyl group, and a naphthyl group, and cyclic ether groups such as an epoxy group, a 3,4-epoxycyclohexyl group, and an oxetanyl group.
[0043] The fluoroalkyl group is an alkyl group having from 1 to 16 carbon atoms and substituted with one or more fluorine atoms. In particular, the fluoroalkyl group is preferably a perfluoroalkyl group.
[0044] The fluoroaryl group is an aryl group substituted with one or more fluorine atoms and having from 6 to 20 carbon atoms. In particular, the fluoroaryl group is preferably a perfluoroaryl group.
[0045] These functional groups have relatively good heat resistance. Therefore, the coating 12 containing the compound derived from the coupling agent having these functional groups is not easily denatured even in a high-temperature environment. Therefore, the surface-coated particles 13 are not easily aggregated and do not easily lose fluidity even in a high-temperature environment. As a result, even when reused, the powder 1 for additive manufacturing can be obtained, which can be laminated well and can produce an additive manufactured body 5 with high dimensional accuracy.
[0046] These functional groups also have good hydrophobicity, so the coating 12 containing the compound derived from the coupling agent having these functional groups provides the powder for additive manufacturing 1 with excellent fluidity even in a humid environment.
[0047] As described above, the powder for additive manufacturing 1 according to this embodiment includes metal powder particles (metal particles 11) and coatings 12 provided on the surfaces of the metal particles 11. The coatings 12 contain a compound derived from a coupling agent having a functional group.
[0048] The average particle size of the powder 1 for layered manufacturing is 3.0 μm or more and 30.0 μm or less. The functional group contains a ring-structure-containing group, a fluoroalkyl group, or a fluoroaryl group.
[0049] Such powder 1 for additive manufacturing is resistant to aggregation even in a high-temperature environment and has high fluidity, despite its small average particle size. Therefore, even if the powder 1 for additive manufacturing is reused, it can produce an additive manufacturing object with high dimensional accuracy. Moreover, such powder 1 for additive manufacturing has low hygroscopicity even in a humid environment. Therefore, it is possible to obtain powder 1 for additive manufacturing that has excellent fluidity even in a humid environment.
[0050] The average thickness of the coating 12 is not particularly limited, but is preferably 100 nm or less, more preferably 0.5 nm to 50 nm, and even more preferably 1 nm to 10 nm. This ensures a film thickness necessary to maintain the coating 12.
[0051] The coating 12 may be a multilayer film in which molecules of the above-mentioned compound are stacked in multiple layers, for example, 2 to 10 layers, but is preferably a monolayer of the above-mentioned compound. The thickness of the coating 12, which is a monolayer, can be minimized.
[0052] The monolayer is a film formed by self-organization of a coupling agent. The coupling agent allows molecules having affinity for the surfaces of the metal particles 11 to be densely arranged on the surfaces, so that a film with a thickness of one molecule can be efficiently formed.
[0053] Furthermore, the powder for additive manufacturing 1 according to this embodiment has surface-coated particles 13 provided with coatings 12 derived from a coupling agent having a specific functional group, and therefore has high heat resistance as described above.
[0054] Specifically, when the additive manufacturing powder 1 is heated in air at 200°C for 24 hours, the bulk density reduction rate from before heating is preferably 2.5% or less, more preferably 2.0% or less, and even more preferably 1.0% or less. This sufficiently suppresses denaturation due to heating when the additive manufacturing powder 1 that was not bound in the additive manufacturing method described above is reused. As a result, even when the reused additive manufacturing powder 1 and the newly added additive manufacturing powder 1 are mixed, the difference in fluidity between the two can be suppressed. Therefore, the additive manufacturing powder 1 whose bulk density reduction rate is within the above range is suitable for reuse.
[0055] The bulk density of the powder 1 for additive manufacturing is measured by the method for measuring the apparent density of metal powders specified in JIS Z 2504:2012. The rate of decrease from before heating is calculated by dividing the decrease in the bulk density measured after heating by the bulk density measured before heating. Therefore, if the bulk density increases after heating, the rate of decrease is zero.
[0056] Similarly, when the powder for additive manufacturing 1 according to this embodiment is heated in the atmosphere at 200° C. for 24 hours, the tap density reduction rate from before heating is preferably 10.0% or less, more preferably 5.0% or less, and even more preferably 2.5% or less. This sufficiently suppresses denaturation due to heating when the powder for additive manufacturing 1 that was not bound in the additive manufacturing method described above is reused. As a result, even when the reused powder for additive manufacturing 1 and the newly added powder for additive manufacturing 1 are mixed, the difference in fluidity between the two can be suppressed. Therefore, the powder for additive manufacturing 1 whose tap density reduction rate is within the above range is particularly suitable for reuse.
[0057] The tap density of the powder 1 for layered manufacturing is measured by a powder property evaluation device, Powder Tester (registered trademark) PT-X, manufactured by Hosokawa Micron Corporation. The rate of decrease from before heating is calculated by dividing the decrease in tap density measured after heating by the tap density before heating, from the tap density measured before heating. Therefore, if the tap density increases after heating, the rate of decrease is zero.
[0058] 4. Manufacturing method of powder for additive manufacturing Next, a method for producing a powder for additive manufacturing according to an embodiment will be described. FIG. 12 is a flowchart for explaining the method for producing a powder for layered manufacturing according to the embodiment. The method for producing a powder for additive manufacturing shown in FIG. 12 includes a preparation step S11, a coupling agent reaction step S12, and a coating formation step S13.
[0059] 4.1. Preparation process In the preparation step S11, a metal powder containing metal particles 11 is prepared. The metal particles 11 may be produced by any method, but are preferably produced by an atomization method such as water atomization, gas atomization, or rotary water flow atomization, and are preferably produced by water atomization or rotary water flow atomization. The surfaces of the metal particles 11 produced by these methods are easily covered with hydroxyl groups derived from water. This makes it possible to increase the adhesion of the coating 12, and even if the coating 12 is thin, the fluidity of the surface-coated particles 13 can be sufficiently increased. As a result, an additive manufacturing body 5 having a higher occupancy rate of the metal particles 11 compared to the coating 12 and a smaller shrinkage rate during sintering can be realized.
[0060] 4.2. Coupling agent reaction step In the coupling agent reaction step S12, a coupling agent having a functional group is reacted with the metal powder, thereby adhering the coupling agent to the surfaces of the metal particles 11.
[0061] Examples of this procedure include a procedure in which both the metal particles 11 and the coupling agent are placed in a chamber, and then the chamber is heated (Method 1); a procedure in which the metal particles 11 are placed in a chamber, and then the coupling agent is sprayed into the chamber while stirring the metal particles 11 (Method 2); and a procedure in which water, the coupling agent, and an alkaline solution such as ammonia or sodium hydroxide are added to a primary alcohol such as methanol, ethanol, or isopropyl alcohol, and the mixture is stirred, filtered, and then dried (Method 3).
[0062] Examples of the coupling agent include a silane coupling agent, a titanium coupling agent, and a zirconium coupling agent. The following chemical formula is an example of the molecular structure of a silane coupling agent.
[0063] [ka]
[0064] In the above formula, X is a functional group, Y is a spacer, and OR is a hydrolyzable group, and R is, for example, a methyl group or an ethyl group.
[0065] The hydrolyzable group is, for example, an alkoxy group, a halogen group, etc., and among these, in the case of an alkoxy group, a silanol is generated by hydrolysis. This silanol reacts with the hydroxyl group generated on the surface of the metal particle 11, and the coupling agent adheres to the surface of the metal particle 11.
[0066] The coupling agent may contain at least one such alkoxy group, but preferably contains two or more, and more preferably contains three alkoxy groups as shown in the above formula. In other words, the coupling agent preferably contains a dialkoxy group, and more preferably contains a trialkoxy group. The coupling agent containing the trialkoxy group reacts with the three hydroxyl groups generated on the surface of the metal particles 11. For this reason, the coating 12 derived from the coupling agent has good adhesion to the metal particles 11. In addition, the coupling agent containing the trialkoxy group is also excellent in film-forming properties, so that the coating 12 with excellent continuity can be obtained. Such a coating 12 contributes to further increasing the fluidity of the powder 1 for additive manufacturing.
[0067] Furthermore, in the case of a coupling agent containing a trialkoxy group, even if the functional group is thermally decomposed after the coating 12 is formed, the remainder can continue to cover the surface of the metal particles 11. Specifically, when the functional group is thermally decomposed, hydroxyl groups bonded to the Si atoms are generated instead. The number of these hydroxyl groups is smaller than the number of hydroxyl groups that were initially generated on the surface of the metal particles 11.
[0068] FIG. 13 is a table that shows a schematic diagram of the state of a coupling agent containing a trialkoxy group after hydrolysis and before it reacts with hydroxyl groups generated on the surface of metal particle 11, the state immediately after the formation of a coating, and the state after the functional groups contained in the coating are thermally decomposed.
[0069] As shown in FIG. 13, the trialkoxy group-containing coupling agent reacts with three hydroxyl groups generated on the surface of the metal particle 11, and adheres to the metal particle 11 through hydrogen bonding. Then, in the coating formation step S13 described below, a dehydration condensation reaction occurs, forming covalent bonds to obtain the coating 12. Then, when the functional group is thermally decomposed, the hydroxyl group is generated after the functional group. As a result, the number of hydroxyl groups generated in the coating 12 can be reduced compared to the number of hydroxyl groups initially generated on the surface of the metal particle 11. Therefore, by forming the coating 12, moisture resistance can be maintained even if the functional group is thermally decomposed.
[0070] As described above, examples of the functional group possessed by the coupling agent include a ring-structure-containing group, a fluoroalkyl group, and a fluoroaryl group.
[0071] Among these, examples of coupling agents having a cyclic structure-containing group include coupling agents having an aryl group and coupling agents having a cyclic ether group.
[0072] Further, among these, examples of the coupling agent having an aryl group include: Phenyltrimethoxysilane represented by the following formula (A-1):
[0073] [ka]
[0074] Phenyltriethoxysilane represented by the following formula (A-2):
[0075] [ka]
[0076] Dimethoxydiphenylsilane represented by the following formula (A-3):
[0077] [ka]
[0078] 2,2-dimethoxy-1-phenyl-1-aza-2-silacyclopentane represented by the following formula (A-4):
[0079] [ka]
[0080] etc.
[0081] Examples of coupling agents having a cyclic ether group include 3-glycidoxypropylmethyldimethoxysilane represented by the following formula (A-5):
[0082] [ka]
[0083] 3-glycidoxypropyltrimethoxysilane represented by the following formula (A-6):
[0084] [ka]
[0085] 3-glycidoxypropylmethyldiethoxysilane represented by the following formula (A-7):
[0086] [ka]
[0087] 3-glycidoxypropyltriethoxysilane represented by the following formula (A-8):
[0088] [ka]
[0089] etc.
[0090] Examples of coupling agents having a fluoroalkyl group include: Trimethoxy(3,3,3-trifluoropropyl)silane represented by the following formula (B-1):
[0091] [ka]
[0092] Trimethoxy(1H,1H,2H,2H-tridecafluoro-n-octyl)silane represented by the following formula (B-2):
[0093] [ka]
[0094] Trimethoxy(1H,1H,2H,2H-nonafluorohexyl)silane represented by the following formula (B-3):
[0095] [ka]
[0096] etc.
[0097] Examples of coupling agents having a fluoroaryl group include: Trimethoxy(11-pentafluorophenoxyundecyl)silane represented by the following formula (C-1):
[0098] [ka]
[0099] Pentafluorophenyldimethylchlorosilane represented by the following formula (C-2):
[0100] [ka]
[0101] etc.
[0102] The amount of the coupling agent added is not particularly limited, but is preferably 0.01% by mass to 1.00% by mass, and more preferably 0.05% by mass to 0.50% by mass, relative to the metal particles 11.
[0103] The coupling agent is supplied by being left stationary in the chamber or by being sprayed into the chamber.
[0104] 4.3. Film formation process In the coating formation step S13, the metal particles 11 to which the coupling agent is attached are heated. As a result, a coating 12 is formed on the surface of the metal particles 11, and the powder for additive manufacturing 1 is obtained. In addition, the heating can remove unreacted coupling agent.
[0105] The heating temperature of the metal particles 11 to which the coupling agent is attached is not particularly limited, but is preferably 50° C. to 300° C., and more preferably 100° C. to 250° C. The heating time is preferably 10 minutes to 24 hours, and more preferably 30 minutes to 10 hours. Examples of the atmosphere for the heat treatment include air and inert gas.
[0106] As described above, the method for manufacturing the powder 1 for additive manufacturing according to the present embodiment includes a preparation step S11, a coupling agent reaction step S12, and a coating formation step S13. In the preparation step S11, a metal powder containing metal particles 11 is prepared. In the coupling agent reaction step S12, a coupling agent having a functional group is reacted with the metal powder to adhere the coupling agent to the surface of the metal particles 11. In the coating formation step S13, the metal powder to which the coupling agent is attached is heated to form a coating 12 on the surface of the metal particles 11. This results in the powder 1 for additive manufacturing. The average particle size of the powder 1 for additive manufacturing is 3.0 μm or more and 30.0 μm or less, and the functional group of the coupling agent contains a cyclic structure-containing group, a fluoroalkyl group, or a fluoroaryl group.
[0107] This makes it possible to obtain the powder 1 for additive manufacturing that has excellent fluidity even in a high-temperature environment. Since such powder 1 for additive manufacturing has excellent fluidity regardless of the environment, when the powder layers 31, 32 are formed by the additive manufacturing method, the powder layers 31, 32 can be formed with a uniform thickness. This makes it possible to manufacture an additive manufactured body 5 of a desired shape with high dimensional accuracy by the additive manufacturing method.
[0108] Moreover, the layered object 5 according to this embodiment includes the powder for layered object 1 and a binder that bonds particles of the powder for layered object 1. Such layered object 5 benefits from the high fluidity of the powder for layered object 1 and has high dimensional accuracy.
[0109] Furthermore, the metal sintered body 10 according to this embodiment is a sintered body of the layered product 5. As described above, the layered product 5 has high dimensional accuracy, and therefore, by using this, it is possible to finally manufacture the metal sintered body 10 having high dimensional accuracy.
[0110] The above-described metal sintered body 10 can be used as a material for constituting all or part of, for example, automobile parts, bicycle parts, railroad vehicle parts, ship parts, aircraft parts, and space transport vehicle parts; electronic device parts such as personal computer parts, mobile phone terminal parts, tablet terminal parts, and wearable terminal parts; electrical device parts such as refrigerators, washing machines, and air conditioners; machine parts such as machine tools and semiconductor manufacturing equipment; plant parts such as nuclear power plants, thermal power plants, hydroelectric power plants, refineries, and chemical complexes; watch parts, and decorative items such as metal tableware, jewelry, and eyeglass frames.
[0111] The powder for additive manufacturing, the method for producing the powder for additive manufacturing, the additive manufactured body, and the metal sintered body of the present invention have been described above based on the illustrated embodiments. However, the present invention is not limited to this, and for example, the powder for additive manufacturing and the additive manufactured body of the present invention may be those having any component added to the above-mentioned embodiments.
[0112] Furthermore, the method for producing a powder for layered manufacturing of the present invention may be one in which any step for any purpose is added to the above-described embodiment. EXAMPLES
[0113] Next, specific examples of the present invention will be described. 5. Production of powder for additive manufacturing 5.1. Example 1 First, powder of precipitation hardening stainless steel 17-4PH manufactured by water atomization method was prepared. Then, 100g of the prepared metal powder was pretreated. Next, a solution was prepared by mixing a coupling agent with water, and this solution was sprayed onto the metal powder heated to 200°C by spray coating. After that, the metal powder onto which the solution was sprayed was left to dry. The amount of the coupling agent used was 0.1% by mass of the metal powder.
[0114] 5.2. Examples 2 to 6 Powder for additive manufacturing was obtained in the same manner as in Example 1, except that the production conditions for the powder for additive manufacturing were changed as shown in Table 1.
[0115] 5.3. Comparative Examples 1 to 7 Powders for additive manufacturing were obtained in the same manner as in Example 1, except that the manufacturing conditions for the powders for additive manufacturing were changed as shown in Table 1. The symbols of the chemical formulas shown in Table 1 correspond to the following compounds.
[0116] D-1: Methyltrimethoxysilane D-2: Propyltrimethoxysilane D-3: Decyltrimethoxysilane D-4: Octadecyltrimethoxysilane D-5: Vinyltrimethoxysilane D-6: Aminotrimethoxysilane
[0117] 6. Evaluation of Powders for Additive Manufacturing 6.1.Fillability 50 g of the powder of each Example and Comparative Example was placed in a 50 mL screw cap bottle. The screw cap bottle was then held upright and the height from the bottom to the top of the powder was measured to evaluate the packing property. The packing property was evaluated according to the following evaluation criteria.
[0118] A: The height is 25mm or less. B: Height is more than 25 mm and less than 30 mm C: Height is over 30mm The evaluation results are shown in Table 1.
[0119] 6.2. Tapping ability 50 g of the powder of each Example and Comparative Example was placed in a 50 mL screw cap. The screw cap was then slammed against a desk 10 times. After that, the screw cap was held upright and the height from the bottom to the top of the powder was measured to evaluate the tapping property. The tapping property was evaluated according to the following evaluation criteria.
[0120] A: The height is 19mm or less. B: Height is over 19mm and 25mm or less C: Height is over 25mm The evaluation results are shown in Table 1.
[0121] 6.3. Cohesiveness 50 g of the powder of each Example and Comparative Example was placed in a 50 mL screw-top vial. The screw-top vial was then rotated 10 times around an axis passing through the center of the bottom of the screw-top vial. The agglomeration state of the powder was then observed from outside the screw-top vial, and the agglomeration was evaluated. The agglomeration was evaluated according to the following evaluation criteria.
[0122] A: Coagulation occurs C: No aggregation The evaluation results are shown in Table 1.
[0123] 6.4.Contact angle For each of the powders of the Examples and Comparative Examples, the water contact angle was measured by the following procedure.
[0124] First, double-sided tape was attached to a flat surface. Next, powder was spread on the double-sided tape. Then, the powder was lightly pressed down with a medicine spoon.
[0125] Next, the excess powder was blown off with an air blower. In this manner, a test specimen for measuring the water contact angle was obtained.
[0126] Next, the contact angle of 3 μL of pure water on the measurement specimen was measured by the θ / 2 method using a contact angle measuring device, DropMaster 500, manufactured by Kyowa Interface Science Co., Ltd. The measured contact angle was then evaluated against the following evaluation criteria.
[0127] A: The contact angle is 110° or more. B: The contact angle is 95° or more and less than 110°. C: Contact angle is 80° or more and less than 95° D: Contact angle is less than 80° The measurement results are shown in Table 1.
[0128] 6.5. Bulk density For the powders of each of the Examples and Comparative Examples, the bulk density was measured by the method for measuring the apparent density of metal powders specified in JIS Z 2504:2012.
[0129] 6.6.Tap Density The tap density of the powders of each Example and Comparative Example was measured using a powder property evaluation device, Powder Tester (registered trademark) PT-X, manufactured by Hosokawa Micron Corp. The number of taps was 125.
[0130] 6.7.Heat resistance The powders of each Example and Comparative Example were subjected to a heat treatment in an air atmosphere at 200°C for 24 hours. Next, the powders after the heat treatment were measured again for packing property, cohesiveness, contact angle, bulk density, and tap density. The measured values were then evaluated according to the above-mentioned evaluation criteria. The evaluation results are shown in Table 1.
[0131] The evaluation criteria for bulk density and tap density are as follows. In the following evaluation criteria, the decrease is the difference between the value after heat treatment and the value before heat treatment, which is taken as 100%.
[0132] <Bulk density evaluation criteria> A: The decrease due to heat treatment is 1.0% or less. B: The decrease due to heat treatment is more than 1.0% and 2.5% or less. C: The decrease due to heat treatment is more than 2.5%.
[0133] <Evaluation criteria for tap density> A: The decrease due to heat treatment is 2.5% or less. B: The decrease due to heat treatment is more than 2.5% and 5.0% or less. C: The decrease due to heat treatment is more than 5.0%.
[0134] [Table 1]
[0135] As shown in Table 1, the powders for additive manufacturing of each Example had better packing properties, contact angles, bulk densities, and tap densities than the powders of each Comparative Example, not only before but also after heat treatment. Therefore, it was recognized that the powders for additive manufacturing of each Example had excellent fluidity even in a high-temperature environment.
[0136] The above contact angle is preferably 110° or more. Powders for additive manufacturing that achieve such a contact angle have particularly low hygroscopicity and therefore exhibit good fluidity even in humid environments.
[0137] Moreover, the measurement results of the bulk density of the powders of Example 1, Reference Example, and Comparative Example 1 are shown in Fig. 14. Fig. 14 is a graph comparing the bulk density of the powder of Comparative Example 1, the powder of Reference Example, and the powder of Example 1. The powder of Reference Example is a powder in which a coating containing silica is formed on the surface of metal particles.
[0138] 14, it was confirmed that the powder of Example 1 had a higher bulk density than not only the powder of Comparative Example 1 but also the powder of the Reference Example. This shows that the powder of Example 1 has good fluidity. The powders of other Examples and Comparative Examples also showed the same tendency as the powder of Example 1 and the powder of Comparative Example 1.
[0139] In addition, the change in bulk density of the powder was measured when the heat treatment time was changed. The measurement results are shown in Figure 15. Figure 15 is a graph showing the relationship between the bulk density of the powder of Example 1 and the powder of Comparative Example 1 and the heating time, with the heat treatment time on the horizontal axis and the bulk density on the vertical axis.
[0140] As shown in FIG. 15, in the powder of Example 1, even if the processing time of the heat treatment is extended, the decrease in bulk density is suppressed, and the bulk density increases. Therefore, it is understood that the flowability of the powder of Example 1 is unlikely to decrease even if the powder placed in a high-temperature environment is repeatedly reused. On the other hand, in the powder of Comparative Example 1, the bulk density decreases according to the heating time, and therefore, it is understood that the flowability is likely to decrease when placed in a high-temperature environment. In addition, the powders of other Examples and other Comparative Examples also showed the same tendency as the powder of Example 1 and the powder of Comparative Example 1.
[0141] 16 shows the results of measuring the tap density of the powders of Example 1, Reference Example, and Comparative Example 1. FIG. 16 is a graph comparing the tap density of the powder of Comparative Example 1, the powder of Reference Example, and the powder of Example 1.
[0142] 16, it was confirmed that the powder of Example 1 had a higher tap density than not only the powder of Comparative Example 1 but also the powder of the Reference Example, which indicates that the powder of Example 1 has good fluidity. [Explanation of symbols]
[0143] Reference Signs List 1... Powder for additive manufacturing, 2... Additive manufacturing apparatus, 4... Binder solution, 5... Additive manufacturing body, 10... Metal sintered body, 11... Metal particles, 12... Coating, 13... Surface-coated particles, 21... Apparatus body, 22... Powder supply elevator, 23... Modeling stage, 24... Coater, 25... Solution supply section, 31... Powder layer, 32... Powder layer, 41... Binder layer, 42... Binder layer, 211... Powder storage section, 212... Modeling section, S01... Powder layer formation process, S02... Binder solution supply process, S03... Repeating process, S11... Preparation process, S12... Coupling agent reaction process, S13... Coating formation process
Claims
1. A powder for additive manufacturing used to form a powder layer for additive manufacturing, A metal powder composed of an Fe-based alloy, a Ni-based alloy, or a Co-based alloy; a coating provided on a surface of a particle of the metal powder, the coating containing a compound formed by reacting a coupling agent having a functional group and a hydrolyzable group with the particle surface; Equipped with The average particle size is 3.0 μm or more and 30.0 μm or less, The functional group contains a cyclic structure-containing group, a fluoroalkyl group, or a fluoroaryl group, the compound contains a covalent bond formed by a dehydration condensation reaction between a hydrolyzate of the hydrolyzable group and a hydroxyl group formed on the particle surface, A powder for additive manufacturing, characterized in that when the powder is spread on a double-sided tape to form a test specimen, the test specimen has a water contact angle of 95° or more.
2. The powder for additive manufacturing according to claim 1 , wherein the coating is a monomolecular film of the compound.
3. 3. The powder for additive manufacturing according to claim 1 or 2, which, when heated in air at 200° C. for 24 hours, exhibits a reduction in bulk density of 2.5% or less compared to before heating.
4. 4. The powder for layered manufacturing according to claim 1, which has a tap density reduction rate of 10.0% or less when heated in air at 200°C for 24 hours.
5. The powder for additive manufacturing described in any one of claims 1 to 4, wherein the coupling agent is a silane coupling agent and the hydrolyzable group is an alkoxy group.
6. The powder for additive manufacturing described in any one of claims 1 to 4, wherein the covalent bond is a Si-O bond.
7. 1. A method for producing an additive manufacturing powder used to form a powder layer for additive manufacturing, comprising the steps of: preparing a metal powder composed of an Fe-based alloy, a Ni-based alloy, or a Co-based alloy; reacting a coupling agent having a functional group with the metal powder to adhere the coupling agent to the surfaces of the particles of the metal powder; a step of heating the metal powder to which the coupling agent is attached, forming a coating on the surface of the particles, and obtaining the powder for additive manufacturing; having The average particle size of the powder for additive manufacturing is 3.0 μm or more and 30.0 μm or less, The functional group contains a cyclic structure-containing group, a fluoroalkyl group, or a fluoroaryl group, A method for producing powder for additive manufacturing, characterized in that when the powder for additive manufacturing is spread on a double-sided tape to form a test specimen, the contact angle of water of the test specimen is 95° or more.
8. The method for producing a powder for layered manufacturing according to claim 7 , wherein the coupling agent contains a trialkoxy group.
9. The method for producing powder for additive manufacturing according to claim 7 or 8, wherein the metal powder is produced by water atomization or rotary water jet atomization.
10. The powder for layered manufacturing according to any one of claims 1 to 6, A binder that binds particles of the powder for additive manufacturing together; An additive manufacturing object comprising:
11. A metal sintered body, which is a sintered body of the layered manufacturing body according to claim 10.
Citation Information
Patent Citations
Iron base powdery mixture for powder metallurgy, its producing method and method of producing compact
JP2001254102A
Surface treatment metal powder for electron beam type 3D printer and manufacturing method therefor
JP2017025392A
Surface additive for three-dimensional metal printing compositions
JP2020164808A
Metal powders with improved flowability
US8894739B1